Teras Philosophy: The Concept of Stoicism in Guiding Modern Life and Islamic Education - Gusti, Yelliza MA; AM, Rusydi; Saputra, Riki (Al-Mudarris, 2025)
Teras philosophy, known as Stoicism, is one of the ancient Greek philosophical schools that emphasizes wisdom, self-control, and acceptance of the reality of life. In modern life full of challenges and uncertainties, the principles of Stoicism offer practical guidance to achieve inner peace and mental resilience. This article aims to examine the basic concepts of Stoicism and their relevance in dealing with the dynamics of life today, and relate them to Islamic education. Stoicism teaches the importance of distinguishing between things we can control and those we cannot, and focuses on developing virtues as the core of a meaningful life. In the context of Islamic education, Stoicism's values of wisdom, patience, and self-control can be integrated to strengthen students' character, morals, and spiritual resilience. This research uses a descriptive-analytical qualitative approach by reviewing literature from various sources, including Stoic texts and Islamic literature, to analyze the similarity of their basic principles. Thus, this article not only provides insights into the application of Stoicism in daily life, but also proposes the potential integration of Stoic values in Islamic education to form individuals who are wiser and more resilient to the pressures of life.